Antibacterial Activity Of Toothpaste Formulation Containing Spirulina platensis Extract Against Streptococcus mutans - Dharma Canti, Distca Putri; Lestari Vidyahayati, Indah; Natania Renata Purnomo, Brigitta (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Background: The main bacteria involved in the formation of dental caries is Streptococcus mutans (S. mutans). One approach to reduce the growth of S. mutans bacterial colonies is by brushing teeth with toothpaste containing antibacterial agent. The commonly used antibacterial agent is chlorhexidine, which is the gold standard chemical in reducing the colonization of S. mutans bacteria and other oral biofilms. However, over time, it causes various side effects, thus necessitating the search for alternative natural ingredients. One ofÂ potential ingredient with antibacterial agent is the Spirulina platensis, which contains secondary metabolites known to inhibit the growth of pathogenic bacteria. Thus, Spirulina platensis can be added to toothpaste as an antibacterial agent. Method: This study employed an experimental laboratory design with a post-test-only control group design. The study consisted of 7 treatments with 5 replications. Antibacterial activity was tested using the agar diffusion method by observing the average diameter of the inhibition zone formed. Data were analyzed using parametric one-way ANOVA. Discussion and Results: In this study, toothpaste with Spirulina platensis extract at concentrations of 0.25%, 0.5%, 1%, 2%, and 3% can inhibited the growth of S. mutans with average inhibition zone diameters of 20.4 mm, 20.8 mm, 21.8 mm, 22.3 mm, and 22.7 mm. The one-way ANOVA parametric test results showed a value of p<0.05, indicating a significant difference in the antibacterial activity of S. mutans in all treatment groups. Conclusion: Toothpaste formulations with Spirulina platensis extract have antibacterial activity against S. mutans bacteria.